COMPARATIVE ANALYSIS OF EMPLOYEE ENGAGEMENT BETWEEN CROSS GENERATION EMPLOYEES - Emilia, Sindi Budi (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2025)
The study aims to comparative analysis of employee engagement employees across generations of PT X. This study uses simple random sampling techniques because PT X employees numbered 61 people.The results showed that all employee engagement indicators based on Q12 (Gallup) in PT X were included in the engaged category. Employee engagement in PT X is included in the engaged category in accordance with the efforts made by the company to maintain/improve employee engagement.